The Use of Youtube As A Learning Medium For Hindu Religious Education - Raditya Oka Dharma, Ida Bagus Gede; Suasnadi Artha, I Ketut; Suwastawa, Kadek; Sujatindriasih, Ni Luh Putu (International Journal of Multidisciplinary Sciences, 2024)
Youtube as a tool to convey information and a place to work in the learning process. In the learning process of Hindu Religious Education, there are still many teachers who only teach by using the lecture method to reduce students' interest in learning, therefore it is necessary to adjust and creativity from a teacher so that learning is more interesting and not monotonous, one of which is by applying the use of Youtube media. The purpose of this study was to determine the impact of using Youtube as a learning medium for Hindu Religious Education (PAH). This study used a qualitative design with the location setting being SMP AMI Denpasar. The data collection techniques used in this study were observation, interview and documentation. The results of this study are: (1) The learning process of Hindu religious education can facilitate the search for information and knowledge transfer; (2) Develop creativity in the use of technology for smooth learning; (3) Improve teacher competence in the use of Youtube media, especially in PAH subjects, and (4) Transform schools into creative, innovative and dynamic learning institutions so that students are motivated, always curious in PAH learning. The use of Youtube as a learning medium for Hindu religious education requires the creativity of teachers and students in its development in order to produce interesting works learned for other students, especially at SMP AMI Denpasar.